FAMILY SUPPORT WITH THE INCIDENCE OF BABY BLUES IN POSTPARTUM MOTHERS IN THE WORKING AREA OF SUGIH WARAS COMMUNITY HEALTH CENTER - Nadia Putri; Arsi, Ranida; Indra Frana Jaya (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Baby blues is an emotional disorder that often occurs in postpartum mothers and can affect the mother's health and the baby's growth and development. Maternal knowledge, social support and family support are thought to play a role in the incidence of baby blues. This research used a quantitative design with a cross sectional approach on 51 postpartum mothers in the Sugih Waras OKI Community Health Center working area in 2025 who were selected using a total sampling technique. Research instruments include questionnaires on maternal knowledge, social support, family support, and the Edinburgh Postnatal Depression Scale (EPDS). Data analysis was carried out univariately and bivariately using the chi-square test (α = 0.05). The prevalence of baby blues was 51.0% (26 respondents). The results of the analysis showed that there was no relationship between maternal knowledge and the incidence of baby blues (p = 0.706), while social support (p = 0.004) and family support (p = 0.003) were significantly related. Mothers with less social support and family support have a higher proportion of baby blues incidents. The prevalence of baby blues in the Sugih Waras OKI Community Health Center working area is relatively high, with social support and family support being significantly related, while maternal knowledge does not show a significant relationship